Alternative Anaphylactic Routes: The Potential Role of Macrophages - Escribese, María M.; Rosace, Domenico; Chivato, Tomas; Fernández, Tahia D.; Corbí, Angel L.; Barber, Domingo (Frontiers in Immunology, 2017)
Anaphylaxis is an acute, life-threatening, multisystem syndrome resulting from the sudden release of mediators from effector cells. There are two potential pathways for anaphylaxis. The first one, IgE-dependent anaphylaxis, is induced by antigen (Ag) crosslinking of Ag-specific IgE bound to the high-affinity IgE receptor (FcεRI) on mast cells and basophils. The second one, IgG-dependent anaphylaxis is induced by Ag crosslinking of Ag-specific IgG bound to IgG receptors (FcgRI, FcgRIIA, FcgRIIB, FcgRIIC, FcgRIIIA) on macrophages, neutrophils and basophils. Macrophages exhibit a huge functional plasticity and are capable of exerting their scavenging, bactericidal and regulatory functions under a wide variety of tissue conditions. Herein, we will review their potential role in the triggering and development of anaphylaxis. Thereby, macrophages, among other immune cells, play a role in both anaphylactic pathways: 1) by responding to anaphylactic mediators, secreted by mast cells after specific IgE crosslinking, or 2) by acting as effector cells in the anaphylactic response mediated by IgG. In this review, we will go over the cellular and molecular mechanisms that take place in the above-mentioned anaphylactic pathways and will discuss the clinical implications in human allergic reactions.